Pour une esthétique de la réception en histoire des idées politiques - Clément Rodier (Sillages Critiques)
Can literature inspire political science? In this article, we would like to show that the paradigm of reception aesthetics, derived from literary theory, demonstrates its heuristic relevance for the history of political thought, so much so that it renews its conception. The history of political thought is based, in fact, on some as-yet-unthought: the aesthetic nature of political ideas. Most of the time, these ideas are contained in works that are read, commented on and interpreted. The hermeneutic approach of reception aesthetics thus makes it possible to reveal the centrality of interpretation in the theoretical and historical significance of a “work of thought”. It encourages, at the same time, a sustained dialogue with political ideas, which is likely to unleash all their potential.